INTEGRASI AGAMA DAN SAINS DALAM PERSPEKTIF ZIAUDDIN SARDAR - Mawar Fita Sari; Amril Amril; Eva Dewi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Many people think that science and religion have their respective positions where science in obtaining truth is based on obtaining epistemological data through several studies. This research is research that discusses religious integration and the efforts made by Ziauddin Sardar and his group to formulate parameters for Islamic Science as an alternative solution to modern science. This research is a type of library research to describe the integration of religion and science from Ziauddin Sardar's perspective. Meanwhile, the method used is analytical descriptive, which is a method used systematically to describe all results related to the main problem. With this analytical descriptive method, it is hoped that Islamic science parameters will be found which can be an alternative solution to the currently developing scientific system. The results of this research on Islamic science explain that according to Ziauddin Sardar, he developed a system of terms which was the basis for his Islamization of science project, which included Tauhid, Khilafah, Worship, Ilmu, Halal, Haram, Fair, Zalim, Istislah, and Dhiya'.